Ensuring our children can hear: are we doing enough? - Sidek, Dinsuhaimi (IIUM Press, 2025)
Hearing loss is one of the most common congenital conditions worldwide, yet it remains underrecognized and often neglected. According to the World Health Organization (WHO) 2021 report, an estimated 34 million children globally experience disabling hearing loss. In the United States, congenital deafness occurs in 2 to 3 per 1,000 live births, with an even higher prevalence among Neonatal Intensive Care Unit (NICU) admissions1. A study by the Ministry of Health Malaysia (MOH) reported a prevalence of 11 per 1,000 live births over a two-year period (2013–2014), highlighting the significance of this issue2.